2019
DOI: 10.1002/jlb.mr0618-224rr
|View full text |Cite
|
Sign up to set email alerts
|

From the “missing self” hypothesis to adaptive NK cells: Insights of NK cell-mediated effector functions in immune surveillance

Abstract: The original discovery of NK cells approximately 40 yr ago was based on their unique capability to kill tumor cells without prior sensitization or priming, a process named natural cytotoxicity. Since then, several studies have documented that NK cells can kill hematopoietic and nonhematopoietic cancer cells. NK cells also recognize and kill cells that have undergone viral infections. Besides natural cytotoxicity, NK cells are also major effectors of antibody‐dependent cell cytotoxicity (ADCC). Therefore, NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 189 publications
(340 reference statements)
0
14
0
Order By: Relevance
“…Among immune cells, NK cells play an important role in recognizing and killing leukemia cells [22,38]. In consequence, NK cell-based immunotherapies have proven to be successful in the treatment of high-risk leukemia [38,43]. However, it is also noticed that not all leukemias, either myeloid or lymphoid, are equally susceptible to these cellbased therapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Among immune cells, NK cells play an important role in recognizing and killing leukemia cells [22,38]. In consequence, NK cell-based immunotherapies have proven to be successful in the treatment of high-risk leukemia [38,43]. However, it is also noticed that not all leukemias, either myeloid or lymphoid, are equally susceptible to these cellbased therapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are important innate immune cells which are closely related to tumorigenesis and metastasis ( 2 ). In vitro and in vivo studies have demonstrated that NK cells can exert a powerful antitumor function without pro-stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cells are important innate immune cells that play essential roles in tumor surveillance ( 1 , 2 ). The function and number of NK cells in patients with cancer are usually diminished compared to healthy individuals ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The exact role for NK cells in autoimmunity is still controversial and data support both pathogenic and protective functions. On one hand, NK cells could directly participate in destroying host tissue, produce high levels of pro-inflammatory cytokines and kill T regulatory cells that normally prevent autoimmunity ( 30 32 ). On the other hand, NK cells do not only have cytotoxic functions, but can also secrete inhibitory cytokines, such as IL-10 and TGFβ, thus leading to a down regulation of the immune system and can block autoreactive CD8 + T cells ( 33 ).…”
Section: The Role Of Nk Cells In Autoimmune Diseasesmentioning
confidence: 99%